Haptoglobin buffers lipopolysaccharides to delay activation of NFκB - Zein, Laura; Grossmann, Josina; Swoboda, Helena; Borgel, Christina; Wilke, Bernhard; Awe, Stephan; Nist, Andrea; Stiewe, Thorsten; Stehling, Oliver; Freibert, Sven-Andreas; Adhikary, Till; Chung, Ho-Ryun (Frontiers in Immunology, 2024)
It has remained yet unclear which soluble factors regulate the anti-inflammatory macrophage phenotype observed in both homeostasis and tumourigenesis. We show here that haptoglobin, a major serum protein with elusive immunoregulatory properties, binds and buffers bacterial lipopolysaccharides to attenuate activation of NFκB in macrophages. Haptoglobin binds different lipopolysaccharides with low micromolar affinities. Given its abundance, haptoglobin constitutes a buffer for serum-borne lipopolysaccharides, shielding them to safeguard against aberrant inflammatory reactions by reducing the amount of free lipopolysaccharides available for binding to TLR4. Concordantly, NFκB activation by haptoglobin-associated lipopolysaccharides was markedly delayed relative to stimulation with pure lipopolysaccharide. Our findings warrant evaluation of therapeutic benefits of haptoglobin for inflammatory conditions and re-evaluation of purification strategies. Finally, they allow to elucidate mechanisms of enhanced immunosuppression by oncofetal haptoglobin.